An Efficient Approach to Describe the Fiber Effect on Mechanical Performance of Pultruded GFRP Profiles - Gribniak, Viktor; Rimkus, Arvydas; Plioplys, Linas; Misiūnaitė, Ieva; Garnevičius, Mantas; Boris, Renata; Šapalas, Antanas (Frontiers in Materials, 2021)
This study focuses on the flexural behavior of pultruded glass fiber-reinforced polymer (GFRP) profiles developed for structural applications. Fiber content is a commonly accepted measure for estimating the resistance of such components, and technical datasheets describe this essential parameter. However, its direct implementation to the numerical simulations can face substantial problems because of the limitations of standard test protocols. Furthermore, the fiber mass percentage understandable for producers is unsuitable for typical software considered the volumetric reinforcement content. This manuscript exemplifies the above situation both experimentally and analytically, investigating two GFRP square hollow section (SHS) profiles available at the market. A three-point bending test determines the mechanical performance of the profiles in this experimental program; a digital image correlation system captures deformations and failure mechanisms of the SHS specimens; a standard tensile test defines the material properties. A simplified finite element (FE) model is developed based on the smeared reinforcement concept to predict the stiffness and load-bearing capacity of the profiles. An efficient balance between the prediction accuracy and computation time characterizes the developed FE approach that does not require specific descriptions of reinforcement geometry and refined meshes necessary for modeling the discrete fibers. The proposed FE approach is also used to analyze the fiber efficiency in reinforcing the polymer matrix. The efficiency is understood as the model’s ability to resist mechanical load proportional to the dry filaments’ content and experimental elastic modulus value. Scanning electron microscopy relates the composite microstructure and the mechanical performance of the selected profiles in this study.